Aspek yuridis program e-karir dalam perspektif hukum ketenagakerjaan - Dhaniar Eka Budiastanti; I Gusti Ngurah Adnyana; Adhinda Dewi Agustine (Jurnal Cakrawala Hukum, 2020)
The obligation of employers to report existing or future job vacancies in their company has been regulated by Presidential Regulation Number 4 of 1980 concerning Mandatory Reporting of Job Vacancies, it is necessary to make adjustments to the needs of the community and it is necessary to synchronize with the Manpower Law, so that it can provide legal protection for job seekers on the availability of job vacancies in an agency. Based on this, the author wants to examine the juridical aspects of the e-career program in the perspective of labor law and legal protection regulated in the Labor regulations against the availability of job vacancies in an agency. This type of research is normative juridical with a statutory approach and a historical approach. The results showed that the juridical aspects of the e-career program in order to reduce the unemployment rate have been regulated in the Law on Manpower as one of the national scale strategic policies. The Law on Manpower has provided legal protection for Job Seekers for the availability of job vacancies in an agency, through Articles 7 and 8 which regulate employment planning and information.How to cite item: Budiastanti, D., Adnyana, I., Agustine, A. (2020). Aspek yuridis program e-karir dalam perspektif hukum ketenagakerjaan. Jurnal Cakrawala Hukum, 11(2), 147-156. doi:https://doi.org/10.26905/idjch.v11i2.4397